Thermoelectric Performance of Bi1.8Sb0.2Te3.0 Alloys under High Pressures - Thi Kim Anh, Do (VNU Journal of Science: Mathematics - Physics; Vol 39 No 3DO - 10.25073/2588-1124/vnumap.4833, 2023)
The pressure eﬀect on the thermopower has been investigated for the Bi 1.8 Sb 0.2 Te 3.0  alloys. We have found an anisotropic pressure dependence on the thermopower for p - and n -type Bi 1.8 Sb 0.2 Te 3.0 at room temperature. Along a -axis, for p -type, the thermopower value increased with increase of pressure at a rate of 13.9 %/Gpa, whereas, along c-axis, itkeeps approximately constant.. The absolue value of the thermopower decreased with pressure along both a - and c -axis for n -type. The power factor increased largely with increase of pressure for p -type Bi 1.8 Sb 0.2 Te 3.0 , while it is approximately constant for n -type.